PERAN GURU PENDIDIKAN AGAMA KRISTEN DALAM MEMBENTUK KARAKTER PEDULI TERHADAP BULLYING SISWA KELAS III SD NEGERI SAYANGAN SURAKARTA - Damai Indah Chrisgita Cahyani (STKIP Subang, 2026)
This study aims to describe the role of Christian Religious Education teachers in developing students' caring character as an effort to prevent bullying among third-grade students at SD Negeri Sayangan Surakarta. This research employed a qualitative descriptive approach with a case study design. The research subjects consisted of one Christian Religious Education teacher, one principal, one third-grade homeroom teacher, and ten third-grade students selected through purposive sampling. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing. The findings indicate that Christian Religious Education teachers play significant roles as educators, role models, mentors, and motivators in fostering students' caring character. The development of caring character was carried out through classroom learning, daily habituation, exemplary behavior, and personal guidance. School support through character-building programs also strengthened the implementation of caring values among students. The study concludes that the active role of Christian Religious Education teachers contributes positively to the development of caring character and helps reduce bullying behavior in the school environment.